Reforma gospodarcza a efektywność rolnictwa - Ratajczak, Klemens (Wydział Prawa i Administracji UAM, 1981)
In the introductory part of the article the author presents the difficult economic situation in Poland and attempts undertaken for overcoming the crisis. Reasons hampering economic growth as well as hopes connected with announced reforms are discussed by the author with reference to agriculture. It results from the analysis that better effects of individual farms are connected with their greater indeipendence in the sphere of economic decisions undertaking as well as consciousness that they work on their own account and at their risk. It resulted in greater interests in production than in socialized farms. The socialized farms have been hedged about with indicators and instructions, many regulations and improper organization. Too big organizational in a from of plants and unions implanited the spirit of officialism among high-qualified cadres leaving them without positive influence an production. The announced economic reform aims at re-introduction of economic independence and responsibility for own results. Equity of prerogatives and encumbrances in all sectores restores the dignity of economic calculus showing the type of a farm, which is better for the society.
The Economic Reform and Effectiveness of Agriculture